CARACTERISATION PHENOTYPIQUE DE LACTOBACILLUS AUTOCHTONES ET EVALUATION DE LEUR POTENTIEL TECHNOLOGIQUE ET PROBIOTIQUE - BENCHENNI, Aicha (My University, 2023)
The aim of the present study is to evaluate the biochemical and physiological characters, technological aptitudes and probiotic potential of some isolates of autochthonous Lactobacillus. First, we confirmed that these bacteria belong to the Lactobacillus genus, by observing their macroscopic appearance, using the catalase test and Gram staining. We then evaluated their biochemical and physiological characters as well as their technological aptitudes. Finally, in order to evaluate their probiotic potential, we tested the antibacterial power of some of these isolates against a pathogenic "S. Aureus" strains isolated from a urine sample taken from a patient suffering from a urinary tract infection. The results revealed that the majority of isolates are homofermentative, capable of growing in hostile conditions. Lactobacilli also exhibit good acidification, proteolytic and lipolytic power. They produce aromas as well as EPS and show strong antibacterial power. In conclusion, it can be said that the Lactobacillus isolates tested show good technological properties and could therefore be exploited in the agri-food industry, particularly the dairy industry. What's more, their use in probiotic therapy, and more specifically in the treatment of urinary tract infections, could represent an alternative to the use of antibiotics.
Keywords: Antibacterial activity; Lactic acid bacteria; Lactobacillus; Probiotic effects; Technological properties